The use of dynamic patches in patients after cardiac surgery in the first stage of late hospital rehabilitation - Antczak, Krzysztof (Journal of Education, Health and Sport, 2019)
Introduction: The use of dynamic slicing effectively supports the rehabilitation process. Thanks to the possibilities and a few contraindications, this method can be used in patients with limitations to physical therapy. Kinesiology Taping, we can use as a method of reducing edema and, at the same time, as a form of increasing the mobility of a given body segment. Aim: The aim of the study is to show that dynamic taping can be used already in patients in the first days after cardiac surgery. The described methods were aimed at: improving the lymphatic system and blood circulation, and consequently reducing edema, reducing pain by loosening fascial and fascial structures, and supporting non-physiologically strained muscles. Conclusions: Kinesiology Taping is a method with 24-hour influence which improves the cardiovascular system. The simplicity of applying the patch, the effectiveness of various slicing techniques, and the hypoallergenicity of the tapes cause that it should be more often used as a separate or complementary method of physiotherapy. The method of dynamic slicing influences the reduction of edema, pain sensation and increase of physical activity among patients. Results: In the study group, edema reduction was observed in all patients, and in 7 patients the measurements showed the same circuits as before cardiac surgery. Pain reduction was reported on average by 2 points on the VAS scale. Discussion: Lietz-Kijak and his colleagues provided patients with orthognathic surgery with two lymphatic applications on both sides of the face-skull. The second test was performed 10 days after the application of the tape. All patients had a reduction in edema and the result was statistically significant. The use of KinesioTapping following invasive arthroscopy of the knee joint was carried out by Gülenç together with co-researchers. The authors have not noted statistically significant changes in the reduction of edema. This may be due to too short a time with the tape being applied. Bialoszewski in the presented study examined 24 patients in whom similar results were presented to those presented in the above work. The results were statistically significant.